2008
DOI: 10.1093/ndt/gfn368
|View full text |Cite
|
Sign up to set email alerts
|

Renal contribution to thermolability in rats: role of renal nerves

Abstract: Speculatively, it may be suggested that one of the renal sensory nerve signal defects associated with decreased kidney energy generation, induced by kidney ablation, may result in an inability to control the body temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Nevertheless, in the present study, BT had a significant predictive value among cats with AKI. It is well known that the kidney plays a role in thermogenesis, and that nephrectomized animals have lower core temperature; in these circumstances, it is quite probable that hypothermia might occur due to renal disease. Additionally, in an experimental study, hypothermia has been found to induce ultrastructural changes in renal tubular cells and these changes were similar to acute tubular necrosis .…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in the present study, BT had a significant predictive value among cats with AKI. It is well known that the kidney plays a role in thermogenesis, and that nephrectomized animals have lower core temperature; in these circumstances, it is quite probable that hypothermia might occur due to renal disease. Additionally, in an experimental study, hypothermia has been found to induce ultrastructural changes in renal tubular cells and these changes were similar to acute tubular necrosis .…”
Section: Discussionmentioning
confidence: 99%
“…As previously defined, the temperature register obeys a nonlinear and randomized model (24). Thus, by a chaotic solution to a deterministic equation, we mean a solution whose outcome is very sensitive to initial conditions and whose evolution through phase space appears to be quite random.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the CNS has been demonstrated in the control of thermal and metabolic homeostasis in mammals (9,24). It is well known that thermal control pathways involve central and peripheral afferent nerve stimuli arriving into the hypothalamic preoptic area and efferent neural and humoral signaling control on thermogenesis and heat loss.…”
Section: Discussionmentioning
confidence: 99%
“…The uniform body temperature in endothermic species is maintained by thermogenesis, which is directly related to the cellular metabolism . Experimental studies revealed that the kidney has a great contribution in thermoregulation . In fact, for more than 50 years, it has been recognized that only a small portion of the energy consumed by the kidneys is used for the ionic and molecular osmotic transfer …”
Section: Introductionmentioning
confidence: 99%
“…Lutaif et al revealed the important role of kidneys in the body thermoregulation. Their experiments were conducted with Sprague‐Dawley rats, which were subjected to surgeries to simulate renal insufficiency, like the bilateral renal denervation and the partial nephrectomy (renal mass reduction by ablation).…”
Section: Introductionmentioning
confidence: 99%